(untitled) (Cambridge, UK, 2003)
This examination of the six states and two self-governing territorial, as well as national, governments reveals the variety and innovation which characterizes the government and politics of the Australian federation. Chapters by leading scholars in the field merge information and analysis for the specialist as well as the general reader. The work is an invaluable source for reference and teaching to anyone concerned with Australian politics.
Keywords: Federal government,Central-local government relations,Australia |x Politics and government,Chính phủ liên bang,Quan hệ chính quyền giữa trung ương và địa phương,Nước Ức; Chính trị và chính phủ; 1945-,1945-; Australia,Australia,Nước Úc,Nước Úc